Architecture design and standardization progress of 5G network - Hao ZHU; Fei XIANG (Dianxin kexue)
The industry has been more and more aware of the important value of network technologies to the 5G system since the vision and the concept of 5G has become clear and focused. Taking higher performance and efficiency as its objective，5G network is about to reconstruct the entire architecture and service provision system to meet the demands of 5G KPIs，scenarios and operations. A top-down design method was introduced which firstly identified the relationships between 5G requirements and technology challenge on legacy network and deduced the development direction of 5G architecture，then the 5G high-level framework of network architecture and infrastructure were raised and the architecture solution for each network function plane and the key network service named as network slicing were proposed in detail. Finally，the standardization progress in main SDOs was summarized. The solution raised can match the 5G service and operational requirements and give an active impetus to the subsequent 5G network research.